Shape-Up and Eat Right Families Pilot Program: Feasibility of a Weight Management Shared Medical Appointment Model in African-Americans With Obesity at an Urban Academic Medical Center - Srivastava, Gitanjali; Palmer, Kenya D.; Ireland, Kathy A.; McCarthy, Ashley C.; Donovan, Kate E.; Manders, Aaron J.; McDougal, Juhee; Lenders, Carine M.; Apovian, Caroline M. (Frontiers in Pediatrics, 2018)
Objectives Disparities in obesity care exist among African-American children and adults. We sought to test the feasibility of a pilot program, a 1-year family-based intervention for African-American families with obesity [shape up and eat right (SUPER)], adopting the shared medical appointment model (SMA) at an urban safety net hospital. Outcomes Primary outcomes: (1) family attendance rate and (2) program satisfaction. Secondary outcomes: change in body mass index (BMI), eating behaviors, and sedentary activity. Methods Adult parents (BMI ≥ 25 kg/m2) ≥18 years and their child(ren) (BMI ≥ 85th percentile) ages 6–12 years from adult or pediatric weight management clinics were recruited. One group visit per month (n = 12) consisting of a nutrition and exercise component was led by a nurse practitioner and registered dietitian. Height and weight were recorded during each visit. Participants were queried on program satisfaction, food logs and exercise journals, Food Stamp Program’s Food Behavior, and the Expanded Food and Nutrition Education Program food checklists. Results Thirteen participants from lower socioeconomic zip codes consented [n = 5 mothers mean age 33 years, BMI of 47.4 kg/m2 (31.4–73.6 kg/m2); n = 8 children; mean age 9 years, BMI of 97.6th percentile (94–99th percentile); 60% enrolled in state Medicaid]. Average individual attendance was 23.4% (14–43%; n = 13); monthly session attendance rates declined from 100 to 40% by program completion; two families completed the program in entirety. Program was rated (n = 5 adults) very satisfactory (40%) and extremely satisfactory (60%). Pre-intervention, families rated their eating habits as fair and reported consuming sugar-sweetened beverages or sports drinks, more so than watching more than 1 h of television (p < 0.002) or video game/computer activity (p < 0.006) and consuming carbonated sodas (p < 0.004). Post-intervention, reducing salt intake was the only statistically significant variable (p < 0.029), while children watched fewer hours of television and spent less time playing video games (from average 2 to 3 h daily; p < 0.03). Conclusion Attendance was lower than expected though children seemed to decrease screen time and the program was rated satisfactory. Reported socioeconomic barriers precluded families from attending most sessions. Future reiterations of the intervention could be enhanced with community engagement strategies to increase participant retention.